Pendidikan Kesadaran Lingkungan melalui Pembelajaran Surat Al-A’raf:56 - Khoirun Iin; Didik Agus Dewantoro; Azizah Khoirun Nissa; Septi Fitriani; Susi Fitriana (Jurnal Abdikarya Pembangunan, 2023)
Abstract: Nurul Ulum TPA Santri are less aware of the environment, and have a low understanding of recitation and memorization of the Qur'an. The students need a program to understand the Al-Qur'an that is more comprehensive which includes memorization, tajwid and the meaning of environmentally conscious values in the verses of the Al-Qur'an. This service uses the Participated action research method. The action taken aims to increase the understanding of recitation, memorization and meaning of Surah Al-A'raf: 56. The action was carried out by providing material on tajwid knowledge and meaning in Surah Al-A'raf: 56. Then practicing tajwid in the process of memorizing letters and practicing the value of environmental awareness in the activities of students at the TPA. As a result, the students are able to memorize QS; Al-A'raf: 56 with recitation and know its meaning. In addition, the behavior that appears is to protect the environment by disposing of garbage in its place. The evaluation illustrates the lack of participation of the santri guardians in making environmentally conscious changes at the TPA. Furthermore, efforts are needed to increase the active participation of santri guardians and synergy between education at the TPA and at home to maintain environmentally conscious behavior as a habit for the santri in their lives. Keywords: Al-A'raf: 56, Environmental awareness, Santri, TPA Abstract: Santri TPA Nurul Ulum kurang berkesadaran lingkungan, serta memiliki pemahaman tajwid dan tingat hafalan Qur’an yang rendah. Para santri membutuhkan program memahami Al-Qur’an yang lebih menyeluruh yang mencakup hafalan, tajwid dan pemaknaan nilai berkesadaran lingkungan dalam ayat Al-Qur’an. Pengabdian ini menggunakan metode Participated action research . Aksi yang dilakukan bertujuan meningkatkan pemahaman tajwid, hafalan dan pemaknaan surat Al-A’raf:56. Aksi dilaksanakan dnegan memberikan materi pengetahuan tajwid dan makna dalam surat Al-A’raf:56. Kemudian mempraktikkan tajwid dalam proses hafalan surat dan mempraktikkan nilai kesadaran lingkungan pada aktivitas santri di TPA. Hasilnya, para santri mampu menghafalkan QS;Al-A’raf:56 dengan tajwid dan mengetahui maknanya. Selain itu perilaku yang nampak adalah lebih menjaga lingkungan dengan membuang sampah pada tempatnya. Evaluasi menggambarkan kurangnya keikutsertaan wali santri dalam melakukan perubahan berkesadaran lingkungan di TPA. Selanjutnya diperlukan usaha untuk meningkatkan partisipasi aktif wali santri dan sinergi antara pendidikan di TPA dan dirumah untuk menjaga perilaku berkesadaran lingkungan menjadi kebiasaan para santri dalam kehidupannya. Keywords: Al-A’raf:56, Kesadaran lingkungan, Santri, TPA